Reappraising the psychosomatic approach in the study of “chronic orofacial pain”: looking for the essential nature of these intractable conditions - Toyofuku, Akira; Matsuoka, Hirofumi; Abiko, Yoshihiro (Frontiers in Pain Research, 2024)
As Burning mouth syndrome(BMS) and Atypical odontalgia(AO) continues to remain a complex pathophysiology lacking explicit treatment protocol, clinicians are only left delving for appropriate solutions. Oversimplification solves nothing on what bother us in clinical situation with BMS or AO. It is important to treat a complicated phenomenon as complex. We should keep careful observations and fact-finding based on pragmatic approach towards drug selection and prescription with regular follow up. We also need to assess long term prognosis of treatment with meticulous selection of sample size and characteristics. Further investigation of BMS and AO with psychosomatic perspective has the potential to provide new insight into the interface between brain function and “Chronic orofacial pain (COFP)”.